2017
DOI: 10.1111/fwb.12888
|View full text |Cite
|
Sign up to set email alerts
|

Do trout respond to riparian change? A meta‐analysis with implications for restoration and management

Abstract: SUMMARY1. There are strong conceptual links between riparian zones and freshwater fish via riparian influences on water quality, habitat quality and availability, and trophic dynamics. Many of the world's riparian zones are, however, severely degraded, and the key functions they provide for fish are lost or compromised. In response to their ongoing degradation, extensive works are underway globally to restore the structure and function of riparian zones. Despite intense effort, we lack clear empirical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 84 publications
(104 reference statements)
1
25
0
Order By: Relevance
“…), and implementing best agricultural (e.g., stock exclusion, Sievers et al. ; and riparian planting, Cross et al. ) practices—all of which have been previously shown to benefit brook trout populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and implementing best agricultural (e.g., stock exclusion, Sievers et al. ; and riparian planting, Cross et al. ) practices—all of which have been previously shown to benefit brook trout populations.…”
Section: Discussionmentioning
confidence: 99%
“…agricultural (e.g., stock exclusion, Sievers et al 2017;and riparian planting, Cross et al 2013) practices-all of which have been previously shown to benefit brook trout populations. Brook trout populations inhabiting streams in watersheds with extensive impervious surface cover (e.g., Gunpowder-Patapsco 8-digit and associated 12-digit HUCs) will likely benefit from instituting best urban development practices (e.g., capturing of storm-water and sediment runoff) and rehabilitating degraded in-stream habitats (see Yeakley et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…the planting of stands of trees where there were none previously, focus on plantation forestry, looking primarily at the impacts of afforestation with non-native (typically conifer) species on stream chemistry (Friberg, Rebsdorf, & Larsen, 1998). There are a few studies that generally confirm the adverse impacts of afforestation on native aquatic biota (Sievers, Hale, & Morrongiello, 2017;Tierney, Kelly-Quinn, & Bracken, 1998), although this response is not uniform (Quinn, Croker, Smith, & Bellingham, 2009;Tierney et al, 1998). Most afforestation studies have taken place in Europe and New Zealand, with a focus on riparian zones.…”
Section: Revegetationmentioning
confidence: 99%
“…The role of riparian zones in sustaining healthy freshwater ecosystems has received ample research attention (Naiman & Decamps, 1997); however, more research is focused on physical habitat attributes than on biotic indicators, and long-term studies of the biotic impacts of riparian restoration (as opposed to management, often as part of forestry practices) are relatively sparse (Roni, Hanson, & Beechie, 2008;Sievers et al, 2017). Measures of benefits to freshwater ecosystems have often focused on representative species and ecosystem attributesoften measured with indices of biotic integrity or ecosystem functioningand the responses of those attributes to riparian land use (sometimes in comparison with upland land use).…”
Section: Riparian Restorationmentioning
confidence: 99%
See 1 more Smart Citation